Using the trigonometric identity for tan(A + B), prove that tan(3x)=(3tan(x)-tan^3(x))/(1-3tan^2(x))

tan(3x)=tan(2x+x), by using the identity for tan(A+B)=(tan(A)+tan(B))/(1-tan(A)tan(B)),tan(3x)=tan(2x+x)=(tan(2x)+tan(x))/(1-tan(2x)tan(x)), using it again for tan(2x),tan(3x)=tan(2x+x)=([(tan(x)+tan(x))/(1-tan(x)tan(x))]+tan(x))/(1-[(tan(x)+tan(x))/(1-tan(x)tan(x))]tan(x))which simplifies to ([2tan(x)/(1-tan2(x))]+tan(x))/(1-[(2tan(x))/(1-tan2(x))]tan(x))which will further simplify to [(3tan(x)+tan3(x))/(1-tan2(x))]/[(1-3tan2(x))/(1-tan2(x))]which yields [3tan(x)+tan3(x)]/[1-3tan2(x)] which is what we got asked
link to resolution on paper: https://imgur.com/a/YUuaop9

Answered by Ivan R. Maths tutor

8711 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find the turning point of the line y = x^2 + 2x -1


The point P lies on the curve C: y=f(x) where f(x)=x^3-2x^2+6x-12 and has x coordinate 1. Find the equation of the line normal to C which passes through P.


Differentiate with respect to x, y = (x^3)*ln(2x)


Find the stationary points on y = x^3 + 3x^2 + 4 and identify whether these are maximum or minimum points.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences